Venkovní aplikace fotokatalytických materiálů - Šimončičová, Monika (Vysoké učení technické v Brně‎, Antonínská 548/1, 601 90 Brno, http://www.vutbr.cz/, 2019)
This bachelor thesis deals with the evaluation and optimization of the method for the determination of photocatalytic activity of facade coating layers with and without photocatalyst admixture titanium dioxide. The layers are tested by the photooxidation of the organic dyes Acid orange 7 and methylene blue, which are model compounds of pollution. Degradation of organic dyes is monitored by UV-VIS spectrophotometry and evaluated by determination of rate constants and specific photoactivity. The aim is to find out which of the facade coating has the highest photoactivity.
Keywords: photocatalytic activity; methylene blue; facade coating; Titanium dioxide; Acid orange 7